Perspectives in environmental toxicology - Kesari, Kavin Kumar (Springer, 2017)
This book is a valuable contribution to the debate about the harmful effects of environmental toxicants on human health, which is a growing concern in the 21st century. Complementary chapters decipher the phenomena and highlight the latest developments in environmental toxicology, providing readers with a comprehensive overview of environmental toxicology and human health. Since the toxicants in question are not only chemical or biological in nature, but also include man-made electromagnetic fields, the book explores in detail multidisciplinary approaches to environmental toxicology, with a focus on the following five aspects: 1. The effects of man-made electromagnetic fields (RF-EMF) on human health (proposed mechanisms and biological effects and measures). 2. An overview of nanotoxicity, nanomedicine and cancer research. 3. A bio-computational approach to the molecular interaction of environmental carcinogens with DNA. 4. The toxicology of environmental pollutants in the air, dust, soil, water and natural toxins in the environment: exposure and health. 5. Social insects as environmental indicators of ecotoxicological effects in different ecosystems. The book analyzes the carcinogenic, mutagenic, genotoxic and neurotoxic effects of both anthropogenic and natural toxins present in water, soil, air and our surroundings in the form of electro-pollution or electro-smog.
Keywords: Environmental toxicology.; elektronické knihy; electronic books